2011
DOI: 10.1029/2011gl049288
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tropospheric biennial oscillation on mid-tropospheric CO2

Abstract: [1] Mid-tropospheric CO 2 retrieved from the Atmospheric Infrared Sounder (AIRS) was used to investigate CO 2 interannual variability over the Indo-Pacific region. A signal with periodicity around two years was found for the AIRS mid-tropospheric CO 2 for the first time, which is related to the Tropospheric Biennial Oscillation (TBO) associated with the strength of the monsoon. During a strong (weak) monsoon year, the Western Walker Circulation is strong (weak), resulting in enhanced (diminished) CO 2 transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Variations of CO 2 seasonal cycle amplitudes are closely related to carbon exchange with the biosphere (Pearman andHyson 1980, 1981;Cleveland et al 1983;Bacastow et al 1985;Keeling et al 1996;Buermann et al 2007). Combining satellite/in situ observations and model simulations, we found that there are Madden-Julian oscillation (MJO), semiannual oscillation (SAO), and tropospheric biennial oscillation (TBO) signals in midtropospheric CO 2 Jiang et al 2012;Wang et al 2011). Combining satellite/in situ observations and model simulations, we found that there are Madden-Julian oscillation (MJO), semiannual oscillation (SAO), and tropospheric biennial oscillation (TBO) signals in midtropospheric CO 2 Jiang et al 2012;Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Variations of CO 2 seasonal cycle amplitudes are closely related to carbon exchange with the biosphere (Pearman andHyson 1980, 1981;Cleveland et al 1983;Bacastow et al 1985;Keeling et al 1996;Buermann et al 2007). Combining satellite/in situ observations and model simulations, we found that there are Madden-Julian oscillation (MJO), semiannual oscillation (SAO), and tropospheric biennial oscillation (TBO) signals in midtropospheric CO 2 Jiang et al 2012;Wang et al 2011). Combining satellite/in situ observations and model simulations, we found that there are Madden-Julian oscillation (MJO), semiannual oscillation (SAO), and tropospheric biennial oscillation (TBO) signals in midtropospheric CO 2 Jiang et al 2012;Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Phases of 24-month component in Table 1 correspond to its maxima in winters of odd years and minima in winters of even years at altitudes 4e8 km. This component may be connected with quasi-biannual oscillations frequently observed in variations of other atmospheric parameters (Wang et al, 2011). Kashin et al (2008) made spectral analysis of the data of about 30-year long ground-based spectroscopic CO 2 observations at IssykKul Monitoring Station (see ISK 242 N00 in WMO WDCGG, 2006) in Kyrgyzstan, 42 N, 77 E, 1650 masl.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous measurements from space (Buchwitz et al, 2005;Chahine et al, 2008;Crevoisier et al, 2009;Eldering et al, 2017;Kuze et al, 2009;Nassar et al, 2011) and ground (Nevison et al, 2008;Newman et al, 2016;Wong et al, 2015;Wunch et al, 2011) have been devoted to monitoring atmospheric CO 2 variability on daily to monthly basis. With midtropospheric CO 2 observations from NASA's spaceborne Atmospheric Infrared Sounder (AIRS) becoming available in the last decade (Chahine et al, 2008), several short-term (intraseasonal to interannual) natural variability have been unveiled, including the tropical intraseasonal variability (with peak-to-peak amplitude~1.5 ppm) related to the Madden-Julian oscillation (MJO) (Li et al, 2010), the semiannual variability (~3 ppm) (Jiang et al, 2012), the biennial variability (~1.0 ppm) related to Asian monsoons (Wang et al, 2011), interannual variability (2-3 ppm) related to the El Niño-Southern Oscillation (Jiang et al, 2010), and polar variability related to the Arctic oscillation and stratospheric sudden warming (Jiang et al, 2010(Jiang et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%